Influence of different soccer-specific maximal actions on physiological, perceptual and accelerometer measurement loads - Dalen, T.; Øverås, Ø.; van den Tillaar, R.; Welde, B.; von Heimburg, E. D. (Open Access Journal of Sports Medicine, 2018)
Background: The aim of this study was to compare the effect of different soccer-specific maximal actions (Continuous run, Sprint, Sprint with change of direction [Sprint COD], Jump and Shot) upon physiological (oxygen uptake and heart rate) and perceptual (rating of perceived exertion [RPE]) responses and accelerometer load. Materials and methods: Ten moderately to well-trained male soccer players volunteered to serve as subjects in this study. A repeated within-subject design was used in which each subject was tested on five occasions on different days, one test each day, during a period of 2 weeks. Each of the five tests had a distance of 900 m and lasted 5 minutes, thus the mean speed for all five tests was 3 m/s. During the test, oxygen uptake, heart rate and accelerometer load were measured. Immediately after each test, RPE was recorded, and after the test, oxygen uptake was measured for 5 minutes while the subject sat in an upright position on a chair. Results: In the comparison of different soccer-specific maximal actions upon physiological and perceptual responses and accelerometer load, this study found that the total accelerometer load was lowest in Sprint and Sprint COD conditions, although the physiological (oxygen uptake and heart rate) and perceptual (RPE) responses were highest in the respective conditions. The Jump condition experienced lower RPE than Sprint and Sprint COD but achieved the highest accelerometer load. Conclusion: Accelerometer load is not a valid measurement for energy costs or RPE but may function as a complementary tool to investigate the player loads during matches and training.